2022
DOI: 10.3390/mi14010013
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Surface Roughness, Burr Formation and Tool Wear in High Speed Micro Milling of Inconel 600 Alloy under Cryogenic, Wet and Dry Conditions

Abstract: Super alloys offer excellent mechanical and chemical properties at elevated temperatures that make them an attractive choice for aerospace, automotive and chemical processing, and marine applications. These alloys are, however, difficult to machine due to their high strength at elevated temperatures, low thermal conductivity and work hardening. In this study, micro milling of Inconel 600 super alloy has been carried out and the effects of the key input parameters (cutting speed, feed rate, depth of cut) on res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…The three-dimensional roughness, S a, of the machined surfaces is illustrated in Figure 5 . Cutting fluid reduces cutting forces through lubrication and cooling functions, thus reducing surface roughness [ 3 , 34 , 35 ]. It indicates that the machined surface roughness under Blasocut and E709 were almost the same, while that of water was larger (about 10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-dimensional roughness, S a, of the machined surfaces is illustrated in Figure 5 . Cutting fluid reduces cutting forces through lubrication and cooling functions, thus reducing surface roughness [ 3 , 34 , 35 ]. It indicates that the machined surface roughness under Blasocut and E709 were almost the same, while that of water was larger (about 10%).…”
Section: Resultsmentioning
confidence: 99%
“…As a typical difficult-to-cut material, the superalloy used for these key components usually has good comprehensive properties, such as high strength, corrosion resistance, and fatigue resistance. In the machining of such hard-to-cut alloys, high cutting temperature, serious tool wear, poor quality, and other problems are often improved by various auxiliary machining methods, such as nitrogen [ 1 ], CO 2 [ 2 ], and cooling machining, by reducing the cutting temperature to improve the surface quality [ 3 ], while the laser-assisted cutting method reduces cutting force but accelerates tool wear [ 4 ]. MQL lubrication improves surface quality, while reducing tool wear and cutting temperature, due to cooling and local lubrication of the cutting zone [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study adopted feed rates below this radius in contrast to titanium alloy Ti-6Al-4V, for which literature reports cutting speeds ranging from 10,000 rpm to 90,000 rpm [6,17,36,37], no previous investigations have been conducted on cutting speeds specific to titanium grade 9. Consequently, this study selected three cutting speed levels (25,50, and 75 m/min) based on Jaffery et al [16]'s work, where 25 and 50 Vc were chosen. Additionally, the recommended depth of cut guidelines provided by Niagra Tool [38] were considered.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Researchers conducted another study on micro-milling Inconel 600 super alloy, commonly used in aerospace and high-temperature applications. They found that cryogenic cooling yielded the best surface roughness and extended tool life, making it a valuable cooling method for machining super alloys [25]. Researchers conducted a study on milling Inconel 718 at conventional speeds, comparing uncoated and coated tools.…”
Section: Introductionmentioning
confidence: 99%
“…Inconel 600 is an austenitic and stable solid-solution nickel-chromium based superalloys. It is non-magnetic, has excellent mechanical properties, and provides the desired combination of high strength and good weldability over a wide temperature range [1][2]. Inconel 600 has excellent resistance to oxidation at high temperatures.…”
Section: Introductionmentioning
confidence: 99%